The Optimal Amount of Attention to Capital Income Risk - Penghui Yin (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies attention allocation behavior of rationally inattentive consumers who have CRRA preferences, face uninsured capital income risk, and suffer from an information-processing capacity constraint. For given attention devoted to capital income risk, we solve for the optimal consumption-saving choices and show that the expected welfare is increasing with capacity, assuming a relative risk aversion degree larger than unity. Furthermore, we solve for attention choice and find that households would pay more attention to capital income risk if they have (i) lower initial wealth endowment, (ii) lower marginal cost of information, (iii) higher prior volatility of capital return, and (iv) higher degree of patience.
Keywords: E13; E21; D81; O16; 330; consumption-saving decision; information-processing constraint; capital-income risk